1984
DOI: 10.1002/j.1552-4604.1984.tb02778.x
|View full text |Cite
|
Sign up to set email alerts
|

A Double‐Blind Parallel Comparison of Ketoprofen, Codeine, and Placebo in Patients with Moderate to Severe Postpartum Pain

Abstract: A total of 152 patients were treated at a single center in a single-dose, double-blind parallel study designed to compare the safety and efficacy of 25, 50, and 100 mg ketoprofen to 90 mg codeine and placebo in patients with moderate to severe postpartum pain (i.e., postepisiotomy, uterine cramping, or cesarean section pain). The analgesic responses to all three doses of ketoprofen and 90 mg codeine were superior to placebo and were not significantly different from each other. No dose-related response was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…The results of the present study corroborate a previous study that did not find any significant difference in analgesic efficacy between an opiate (codeine) and an NSAID (ketoprofen) [18]. Similar to the present findings, those authors reported significantly more adverse effects among patients treated with codeine.…”
Section: Discussionsupporting
confidence: 95%
“…The results of the present study corroborate a previous study that did not find any significant difference in analgesic efficacy between an opiate (codeine) and an NSAID (ketoprofen) [18]. Similar to the present findings, those authors reported significantly more adverse effects among patients treated with codeine.…”
Section: Discussionsupporting
confidence: 95%
“…The lack of a ketoprofen dose response in the dose range below 50 mg [2][3][4] cannot be explained by stereochemical and/or pharmacokinetic aspects.…”
Section: Discussionmentioning
confidence: 94%
“…Furthermore no data on the dose-AUC relationship at doses below 50 mg are available although there are clinical studies showing analgesic activity below 50 mg of the racemate [2][3][4]. However, in this dose range there was no evidence of a ketoprofen dose response [2][3][4]. In the present study we have determined the absolute bioavailability of KT and its enantiomers from an oral formulation of racemic KT (50 mg) as well as pharmacokinetic parameters following oral administration of 12.5, 25 and 50 mg racemic KT to show whether or not stereochemical pharmacokinetic aspects have to be considered for the explanation of the lack of dose response.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…This latter effect of codeine would appear to be dose related and linear, and the time course, like its analgesic activity (Kantor et al, 1966(Kantor et al, , 1984, follows closely its known plasma concentrations (Waife et al, 1975). The minimal effects of codeine in the present study are consistent with previous observations (Redpath & Pleuvry, 1982;Liljequist, 1981).…”
Section: Discussionmentioning
confidence: 99%